2014
DOI: 10.1155/2014/858936
|View full text |Cite
|
Sign up to set email alerts
|

Regional Warming and Emerging Vector-Borne Zoonotic Dirofilariosis in the Russian Federation, Ukraine, and Other Post-Soviet States from 1981 to 2011 and Projection by 2030

Abstract: We analyze through a climatic model the influence of regional warming on the geographical spreading and potential risk of infection of human dirofilariosis in Russia, Ukraine, and other post-Soviet states from 1981 to 2011 and estimate the situation by 2030. The model correctly predicts the spatiotemporal location of 97.10% of 2154 clinical cases reported in the area during the studied period, identified by a retrospective review of the literature. There exists also a significant correlation between annual pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
28
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(53 citation statements)
references
References 19 publications
(32 reference statements)
13
28
0
9
Order By: Relevance
“…The ability of GIS to predict the distribution and epidemiology of dirofilariosis in different geographical areas has been already demonstrated by the empirical epidemiological data obtained at the continental (Genchi et al, 2009;Kartashev et al, 2014), national (Medlock et al, 2007;Simón et al, 2014), and regional (Mortarino et al, 2008;Montoya-Alonso et al, 2015) levels. As demonstrated in our present study, GIS could become an important tool for the management of HWD in endemic and non-endemic countries.…”
Section: Discussionmentioning
confidence: 95%
“…The ability of GIS to predict the distribution and epidemiology of dirofilariosis in different geographical areas has been already demonstrated by the empirical epidemiological data obtained at the continental (Genchi et al, 2009;Kartashev et al, 2014), national (Medlock et al, 2007;Simón et al, 2014), and regional (Mortarino et al, 2008;Montoya-Alonso et al, 2015) levels. As demonstrated in our present study, GIS could become an important tool for the management of HWD in endemic and non-endemic countries.…”
Section: Discussionmentioning
confidence: 95%
“…There were fluctuations in morbidity during the above-mentioned time-period, probably related to thermal fluctuations influencing both the abundance of mosquitoes and the number of yearly generations of Dirofilaria larvae developing in the vectors. 10 Our data suggest that in the Russian Federation and Belarus, almost half of all HSOD cases have an ocular location and that HSOD predominantly affects females; both rates are clearly higher than those observed at the global level. 2 Regarding age, the highest number of cases was found in people aged between 41 and 60 years, similar to the findings of other studies.…”
Section: Discussionmentioning
confidence: 48%
“…10 Additionally, subjective factors such as a lack of awareness of the disease, as well as the low visibility and accessibility of the databases in which cases are collected, may give an altered picture of HSOD, concealing a part of the available information and making this disease a neglected health condition. This, together with the severity of some reported cases, 3 shows the urgent need for the application of uniform criteria to detect and retrieve human cases.…”
Section: Discussionmentioning
confidence: 99%
“…This spreading is attributed to the global warming and the lack of an adequate treatment of pets in some countries (Kartashev et al, 2014). Around 4000 human cases have been reported worldwide, 3500 of which have been diagnosed in Europe, most of them in Ukraine and the Russian Federation during the last 10 years (Kartashev et al, 2014;Sałamatin et al, 2013).…”
mentioning
confidence: 99%
“…This spreading is attributed to the global warming and the lack of an adequate treatment of pets in some countries (Kartashev et al, 2014). Around 4000 human cases have been reported worldwide, 3500 of which have been diagnosed in Europe, most of them in Ukraine and the Russian Federation during the last 10 years (Kartashev et al, 2014;Sałamatin et al, 2013). Ocular cases are the most frequently reported, making up 35% of the human cases described worldwide (Genchi et al, 2011b) and more than 40% of the cases found in Ukraine and the Russian Federation (Avdiukhina et al, 1996;Iliasov et al, 2013).…”
mentioning
confidence: 99%